2004
DOI: 10.1007/s00296-004-0515-4
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis and bone mineral density—what is the ideal tool for measurement?

Abstract: Ankylosing spondylitis (AS) is characterised by chronic inflammation and partial ossification, yet vertebral fractures due to osteoporosis, although common, are frequently unrecognised. The aim of this study was to (1) show the frequency of changes in the progress of osteopenia/osteoporosis in AS depending on duration and stage of the disease and (2) assess the ranking of two different methods of bone density measurement in this clinical pattern. We measured bone density in 84 male and female patients with bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 21 publications
0
40
0
8
Order By: Relevance
“…Çalışmamızda, osteopenisi olan AS'li hastalarda kemik mineral yoğunluğu ile hastalık aktivitesi arasında ilişki bulunmamıştır. AS'de kemik kaybı hem omurgada hem de femur boyun bölgesinde hastalığın erken döneminden başlayarak ileri dönemlerinde de devam eder (10). Özellikle ilaçlara rağmen inflamasyonun engellenemediği ve hastalık süresinin uzun olduğu durumlarda kemik kaybı fazladır (11,12).…”
Section: Discussionunclassified
“…Çalışmamızda, osteopenisi olan AS'li hastalarda kemik mineral yoğunluğu ile hastalık aktivitesi arasında ilişki bulunmamıştır. AS'de kemik kaybı hem omurgada hem de femur boyun bölgesinde hastalığın erken döneminden başlayarak ileri dönemlerinde de devam eder (10). Özellikle ilaçlara rağmen inflamasyonun engellenemediği ve hastalık süresinin uzun olduğu durumlarda kemik kaybı fazladır (11,12).…”
Section: Discussionunclassified
“…Significant positive correlation between QCT results at the lumbar spine and DEXA results at the femoral neck had been reported in the same study (25). Lange et al (2) showed bone mass loss by QCT at the lumbar spine in both early and late AS patients. Nevertheless, lateral lumbar DEXA may be more suitable for serial BMD measurements because it has lower radiation dose than QCT.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory enthesopathy progressing to ossification and ankylosis is the pathologic basis of the disease (1). A considerable decrease in bone mineral density at lumbar spine and femoral neck has been observed in AS (2). Osteoporotic vertebral fracture rates have ranged from 0% to 18% (3).…”
Section: Introductionmentioning
confidence: 99%
“…Ossification is the hallmark of AS and has been linked to aberrant activation of bone morphogenic protein (BMP) and wingless (WNT) signaling. Bone resorption, driven by the impact of inflammation on the bone remodeling cycle, occurs simultaneously, with up to 56% of patients developing systemic osteopenia and some of them systemic osteoporosis (Lange et al, 2005).…”
Section: Bone Ossification and Resorption Processesmentioning
confidence: 99%